Depletion of Key Meiotic Genes and Transcriptome-Wide Abiotic Stress Reprogramming Mark Early Preparatory Events Ahead of Apomeiotic Transition - Shah, Jubin N.; Kirioukhova, Olga; Pawar, Pallavi; Tayyab, Muhammad; Mateo, Juan L.; Johnston, Amal J. (Frontiers in Plant Science, 2016)
Molecular dissection of apomixis - an asexual reproductive mode - is anticipated to solve the enigma of loss of meiotic sex, and to help fixing elite agronomic traits. The Brassicaceae genus Boechera comprises of both sexual and apomictic species, permitting comparative analyses of meiotic circumvention (apomeiosis) and parthenogenesis. Whereas previous studies reported local transcriptome changes during these events, it remained unclear whether global changes associated with hybridization, polyploidy and environmental adaptation that arose during evolution of Boechera might hint as (epi)genetic regulators of early development prior apomictic initiation. To identify these signatures during vegetative stages, we compared seedling RNA-seq transcriptomes of an obligate triploid apomict and a diploid sexual, both isolated from a drought-prone habitat. Uncovered were several genes differentially expressed between sexual and apomictic seedlings, including homologues of meiotic genes ASYNAPTIC 1 (ASY1) and MULTIPOLAR SPINDLE 1 (MPS1) that were down-regulated in apomicts. An intriguing class of apomict-specific deregulated genes included several NAC transcription factors, homologues of which are known to be transcriptionally reprogrammed during abiotic stress in other plants. Deregulation of both meiotic and stress-response genes during seedling stages might possibly be important in preparation for meiotic circumvention, as similar transcriptional alteration was discernible in apomeiotic floral buds too. Furthermore, we noted that the apomict showed better tolerance to osmotic stress in vitro than the sexual, in conjunction with significant upregulation of a subset of NAC genes. In support of the current model that DNA methylation epigenetically regulates stress, ploidy, hybridization and apomixis, we noted that ASY1, MPS1 and NAC019 homologues were deregulated in Boechera seedlings upon DNA demethylation, and ASY1 in particular seems to be repressed by global DNA methylation exclusively in the apomicts. Variability in stress and transcriptional response in a diploid apomict, which is geographically distinct from the triploid apomict, pinpoints both common and independent features of apomixis evolution. Our study provides a molecular frame-work to investigate how the adaptive traits associated with the evolutionary history of apomicts co-adapted with meiotic gene deregulation at early developmental stage, in order to predate meiotic recombination, which otherwise is thought to be favourable in stress and low-fitness conditions.